Dipeptide and phenolic compounds from the leaves of Cudrania tricuspidata Carr. Bur and their cytotoxic activity - Tuan Anh, Hoang Le; Trang, Do Thi; Tuan, Do Thanh; Duc, Tran Minh; Phuong Anh, Tran Thi; Hai Yen, Duong Thi; Nhiem, Nguyen Xuan; Minh, Chau Van; Tai, Bui Huu; Kiem, Phan Van (Vietnam Journal of Chemistry, 2015)
By various chromatographic separations, two peptides, aurantiamide acetate (1) and aurantiamide (2), and two phenolic compounds, (E)-p-coumaric acid (3) and gatrodin (4), were isolated from methanol extract of the Cudrania tricuspidata leaves. Their structures were determined by 1D-, 2D-NMR spectra and in comparison with the reported data. Aurantiamide exhibited significant cytotoxic activity on HL-60 leukemia human cancer cell line with IC50 value of 20.41 mM. Compounds 1 and 2 were reported from genus Cudrania for the first time. Keywords. Cudrania tricuspidata, aurantiamide, aurantiamide acetate.